Evaluation of the Correlation Between Nursing Students' General Attitudes Toward Artificial Intelligence, Literacy and Anxiety Levels: A Descriptive and Correlational Study. - EMİNOĞLU, Ayşe; KUŞLU, Sebahat; ÇAKIR, Beşir (Turkiye Klinikleri Journal of Nursing Sciences, 2025)
Objective: This study aims to determine the relationship between nursing students' general attitudes toward artificial intelligence, literacy, and anxiety levels. Material and Methods: The study was conducted using a descriptive-correlation-seeking design. The sample consisted of 414 nursing students at a state university. The "Personal Information Form", "General Attitude Towards Artificial Intelligence Scale (GAAIS)", "Artificial Intelligence Anxiety Scale (AIAS)", and "Artificial Intelligence Literacy Scale (AILS)" were used as data collection tools. Results: The mean age of the students was 21.07±1.84 years; the majority were female (72.7%) and in their first year of education (30.9%). While 44.4% of the students' mothers and 44.0% of their fathers completed primary school 89.6% of the students' mothers were not working, and 78.7% of the students' fathers were working. The mean total scores of the students in the GAAIS, AIAS, and AILS were 65.87±9.42, 49.20±9.24 and 43.04±6.53, respectively. It was found that there was a statistically significant relationship between the GAAIS and the AIAS in a negative direction and a positive direction with the AILS (p=0.001). Conclusion: It was determined that students' general attitudes towards artificial intelligence and artificial intelligence literacy were high, and their artificial intelligence anxiety was at a medium level. Adding courses on artificial intelligence to all students at the university level will help them gain more knowledge about technological innovations and ensure awareness, which will help reduce anxiety levels while strengthening their literacy and general attitudes.